Value-Creating Perspectives and an Intercultural Approach to Curriculum for Global Citizenship - Sharma, Namrata (Journal of Interdisciplinary Studies in Education, 2020)
Several recent scholarly works have challenged the Western dominated paradigm underlying the UNESCO led agenda of global citizenship education. This includes the heavy influence of Enlightenment liberalism. Further discussions must also be centered on integrating non-Western perspectives so that the practice of global citizenship has a more critical and intercultural focus. This paper offers suggestions to develop curriculum for global citizenship based on a study of leaders and their movements, including Wangari Maathai and Daisaku Ikeda who have inspired people to act within their local communities based on their personal values that are rooted in their experiences with being engaged in both Western and non-Western modes of thinking.